Proposed Quality Control Method for Greig Fabric Production on RRC Shuttel Weaving Machine Using FTA-FMEA to Reduce Fabric Defects at PT XYZ - Fadil Abdullah; Iphov Kumala Sriwana (School of Industrial and System Engineering, Telkom University, 2023)
PT XYZ faces challenges in declining product quality due to production defects exceeding the optimaltolerance limit of 2% per period for six consecutive periods. This research aims to identify and addressdefects, offering action strategy recommendations to mitigate and prevent their recurrence during theproduction of grey fabric on RRC shuttle loom machines. The study utilizes an integrated analysis method,combining Fault Tree Analysis (FTA) and Failure Mode and Effect Analysis (FMEA). The researchhighlights five major defect types in grey fabric products, constituting 80% cumulatively. These defectsinclude pickbar issues, ambrol (fraying), tears, broken threads, and skipped weaving. Twelve root causescontributing to these defects in RRC shuttle loom production are identified and evaluated based on theirRisk Priority Number (RPN), categorized into classes A, B, and C with varying risk intensities. Two rootcauses from Class A, constituting 20% cumulatively, are identified as primary defect causes. These issuesinvolve the fit of the weaving reed and discrepancies in the let-off and take-up motion mechanism on theloom machine, each with an RPN value of 648. Action strategy recommendations are provided for thesetwo root causes, collectively contributing to 20% of the overall problem percentage. The objective is toprevent the recurrence of the five major defect types, accounting for 80% of the cumulative percentage.This comprehensive approach aims to rectify the identified issues, ensuring a higher standard of productquality in the textile manufacturing process